Behavioral Inhibition Integrating Theory, Research, and Clinical Perspectives (Springer International Publishing, 2018)
This book examines three decades of research on behavioral inhibition (BI), addressing its underlying biological, psychological, and social markers of development and functioning. It offers a theory-to-practice overview of behavioral inhibition and explores its cognitive component as well as its relationship to shyness, anxiety, and social withdrawal. The volume traces the emergence of BI during infancy through its occurrences across childhood. In addition, the book details the biological basis of BI and explores ways in which it is amenable to environmental modeling. Its chapters explore the neural systems underlying developmental milestones, address lingering questions (e.g., limitations of studying BI in laboratory settings and debatable benefits of self-regulatory processes), and provide recommendations for future research. Key areas of coverage include: Animal models of behavioral inhibition. Social functioning and peer relationships in BI. Attention mechanisms in behavioral inhibition. BI and associative learning of fear. Behavioral inhibition and prevention of internalizing distress in early childhood. The relations between BI, cognitive control, and anxiety. Behavioral Inhibition is a must-have resource for researchers, clinicians, scientist-practitioners, and graduate students across such fields as developmental psychology, psychiatry, social work, cognitive and affective developmental neuroscience, child and school psychology, educational psychology, and pediatrics.